The Semantics of the Verbs of Activity in the “Seasons” by Kristijonas Donelaitis - Lisauskaitė, Agnė; Zubaitienė, Vilma (Respectus Philologicus, 2019)
[full article and abstract in Lithuanian; abstract in English]This paper investigates the semantics of the verbs of activity in the first Lithuanian poem “The Seasons” by Kristijonas Donelaitis. It aims to examine the meanings of the verbs of activity. The research covers 51 verbs, selected from the poem, which are subjected to qualitative content analysis and frame semantics methodology. The verbs which best represent the frames and sub-frames were selected applying the method of the qualitative content analysis. The frames of Work, Damaging, Speak on topic, Motion, Ingestion and Entertainment, evoked by the selected verbs, are examined using the frame semantics methodology. Core and peripheral elements of frames and sub-frames are distinguished. Also, the means of expression, used to convey them, are analyzed. The research has shown that the verbs of activity can form the core of the mentioned frames. However, not all situations found in FrameNet have corresponded with the frames and sub-frames that were analysed in this work.
Keywords: activity; frame semantics; verb